Peran Museum Negeri Medan Dalam Pelestarian Warisan Budaya Multietnis Di Sumatera Utara - Harahap, Dumel Awiyah; Triwibowo Damanik, Tegar; Rivaldi, Alvin; Astari, Novia; Aziz Batu bara, Farhana; Windari, Sri (Dampeng: Journal of Art, Heritage and Culture, 2025)
This study aims to analyze the role of the Medan State Museum in preserving multi-ethnic cultural heritage in North Sumatra. The museum is understood not only as a place for storing historical artifacts, but also as a space for public education and a means of strengthening community cultural identity. This research employs a qualitative approach using a descriptive-analytical method through observation, interviews, and documentation studies. The findings indicate that the Medan State Museum plays an active role in preserving ethnographic collections, representing the cultures of various ethnic groups in North Sumatra, and organizing educational programs as well as cultural exhibitions for the public. However, the museum still faces several challenges, including limitations in human resources, facilities, and low public interest in museum visits. Therefore, innovative, participatory, and sustainable management strategies are required to further optimize the museum’s role in preserving and safeguarding multi-ethnic cultural heritage. [Penelitian ini bertujuan untuk menganalisis peran Museum Negeri Medan dalam pelestarian warisan budaya multietnis di Sumatera Utara. Museum dipahami tidak hanya sebagai tempat penyimpanan koleksi benda bersejarah, tetapi juga sebagai ruang edukasi publik dan sarana penguatan identitas budaya masyarakat. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif-analitis melalui teknik observasi, wawancara, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa Museum Negeri Medan berperan aktif dalam melestarikan koleksi etnografi, merepresentasikan kebudayaan berbagai etnis yang ada di Sumatera Utara, serta menyelenggarakan kegiatan edukasi dan pameran budaya bagi masyarakat. Namun demikian, museum masih menghadapi beberapa tantangan, seperti keterbatasan sumber daya manusia, fasilitas, serta rendahnya minat kunjungan masyarakat. Oleh karena itu, diperlukan strategi pengelolaan yang inovatif, partisipatif, dan berkelanjutan agar peran museum dapat lebih optimal dalam menjaga dan melestarikan warisan budaya multietnis]